2015
DOI: 10.1007/s40746-014-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscopes in Paediatric Anaesthesia

Abstract: The use of videolaryngoscopy is an ever expanding and developing branch of both routine and advanced airway management. An array of 'tried and tested' videolaryngoscopes is increasingly being used routinely in adults. However, due to the anatomical differences between adults and children, the proposed benefits are not readily transferrable without supporting evidence. With an increase in paediatric-sized equipment, the last 10 years has seen a rise in the number of relevant clinical investigations in the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…5 Although a recent study demonstrated that the use of a videolaryngoscope was associated with a higher success rate for tracheal intubation in children when compared with direct laryngoscopy 12 there is currently no single one type of videolaryngoscope shown to be superior to others for children in terms of value or clinical use in all situations. 12,13 It is also of note that intubation aids with bougies and stylets, which are recommended for indirect laryngoscopy, were rarely used in clinical practice in line with a recent trend. 14 To our knowledge, this is the first report on the incidence of failure of securing the paediatric airway using either a tracheal tube or an SGA in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although a recent study demonstrated that the use of a videolaryngoscope was associated with a higher success rate for tracheal intubation in children when compared with direct laryngoscopy 12 there is currently no single one type of videolaryngoscope shown to be superior to others for children in terms of value or clinical use in all situations. 12,13 It is also of note that intubation aids with bougies and stylets, which are recommended for indirect laryngoscopy, were rarely used in clinical practice in line with a recent trend. 14 To our knowledge, this is the first report on the incidence of failure of securing the paediatric airway using either a tracheal tube or an SGA in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Video-laryngoscopy has made an impact in overall successful airway management both in the operating room as well as in intensive care unit. [2134353637] It has the potential to become the first line option for intubation and for difficult airway. Studies have found that video-laryngoscopes (VLs) [Table 2 and Figure 3] are associated with better glottic visualisation, a higher success rate for difficult airways, and a faster learning curve, resulting in a higher success rate for intubations by novice physicians.…”
Section: Videolaryngoscopesmentioning
confidence: 99%
“…13 The difference may be partly due to lack of paediatric videolaryngoscopes in the earlier cases described; intubation trends may change with currently available equipment. 13,14,[82][83][84] Intubation in patients with BBS and with a BE may be difficult but has been described as 'unexpectedly easy … through the separate leaflets' . 56 Airway management in symptomatic laryngeal anomalies may be extremely challenging, and may require a tracheostomy.…”
Section: Airway Management In Bbs and Laryngeal Anomaliesmentioning
confidence: 99%
“…74,89 The current gold standard for elective intubation remains the FOB; however, VL is expected to impact on these recommendations as evidence for their use is increasing in children, including those with a predicted difficult airway. 13,[82][83][84][89][90][91][92][93][94] VL may not always be successful, either because of restricted mouth opening or • VL has an increasing role in paediatric difficult airway management but is not fail-safe…”
Section: The Expected Versus the Unexpected Difficult Airway In Childrenmentioning
confidence: 99%